Building an Inclusive Research Team: The Importance of Team Building and Skills Training. Issue 1 (20th November 2013) - Strnadová, Iva; Cumming, Therese M.; Knox, Marie; Parmenter, Trevor
<x xml:space="preserve">Abstract</x> Background Inclusive research teams typically describe their experiences and analyse the type of involvement of researchers with disability, but the process of building research teams and the need for research training still remain underexplored in the literature. Materials and Method Four researchers with intellectual disabilities and four academic researchers developed an inclusive research team. The team conducted 15 research training sessions, focused on investigating the well‐being of older women with intellectual disabilities. They used mobile technology to support research skills acquisition. Results Findings included the experiences of all team members regarding the team building during training. Conclusions To become an effective inclusive research team, all team members, regardless of ability, need to bring their own experiences and also learn necessary research skills. This paper highlights the need for team building, joint research training among all members of the research team and strategies supporting the peer‐mentoring within the team. Accessible Abstract We are a team of four researchers with intellectual disabilities and four academic researchers without an intellectual disability. Our aim has been to learn about research together. We want to do this so that we can carry out a research project together about how older women with intellectual disabilities live. We have decided to call our team 'Welcome to our Class'. We have been working together for 9 months. In this time we have had 15 research training meetings. We have learned What research is How to work out a research question, that is what we want to find out about How to get information on what we want to find out. Here we thought of interview questions we could ask older women with intellectual disabilities. We are now meeting once a month, and have just begun our research on finding out how older women with intellectual disabilities live. We are now starting to use what we have learned.